The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/jfb14050249
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Biomedical Ti-18Zr-15Nb Alloy by Atomic Layer Deposition and Ag Nanoparticles Decoration

Abstract: Superelastic biocompatible alloys attract significant attention as novel materials for bone tissue replacement. These alloys are often composed of three or more components that lead to the formation of complex oxide films on their surfaces. For practical use, it is desirable to have a single-component oxide film with a controlled thickness on the surface of biocompatible material. Herein we investigate the applicability of the atomic layer deposition (ALD) technique for surface modification of Ti-18Zr-15Nb all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Such structures should exhibit higher adhesion. Thus, we have shown that such complex structures can be obtained in a single ALD process, which simplifies the synthesis and reduces the risk of poor adhesion of Ag nanoparticles [69] and is likely to increase interest in such structures in the future.…”
Section: Advantages Disadvantages and Perspectives Of Aldmentioning
confidence: 98%
See 2 more Smart Citations
“…Such structures should exhibit higher adhesion. Thus, we have shown that such complex structures can be obtained in a single ALD process, which simplifies the synthesis and reduces the risk of poor adhesion of Ag nanoparticles [69] and is likely to increase interest in such structures in the future.…”
Section: Advantages Disadvantages and Perspectives Of Aldmentioning
confidence: 98%
“…This process reduces the recombination of photo-induced carriers at the noble metal/semiconductor interface [67]. Typically, noble metals such as silver [30,68,69] and gold [60] are deposited as nanoparticles on pre-synthesized ALD TiO 2 . While silver has been shown to possess powerful antibacterial properties due to Ag + release, the formation of a Schottky heterojunction at the TiO 2 /Ag interface results in reduced electron-hole recombination rates.…”
Section: Doped Tio 2 and Combined Tiomentioning
confidence: 99%
See 1 more Smart Citation
“…The material was tested on the mesenchymal tumor stem cell line ST-2, showing excellent osteoconductive properties. However, achieving such a thickness in ALD involves an extensive process with multiple cycles. Nevertheless, ultrathin TiO 2 ALD coatings can effectively shade potentially poisonous elements, such as F and V, which can be detrimental to biocompatibility properties, decreasing the ALD process time. In our previous work, it was shown that ALD-modified TNT layers with 5c and 150c of TiO 2 can significantly improve the cell growth and the biocompatibility of WI-38 fibroblasts by 50%, SH-SY5Y neuroblasts by 30%, and MG-63 osteoblasts by 30% compared with the uncoated counterparts. , The comparison to Ti foils with a native and thermal oxide layer was also carried out …”
Section: Introductionmentioning
confidence: 99%